Environment sustainable construction materials for garden-fresh and mechanical properties of high strength self-compacting concrete mixes with diverse mineral admixtures and water binder ratios. (2018) - Lavanya, R.; Murthi, P.; Karthikeyan, V.
An experimental investigation was carried out to study the properties of self-compacting concrete (SCC) prepared with different mineral admixtures and water-binder ratios. The mixes were designed for M60 grade of concrete and prepared with three steps of addition of GGBS and silica fume and were made with four steps of fly ash as partial replacement of fine aggregate. The fresh properties were studied with standard tests. Compressive strength was found at the different ages and the split tensile and flexural tests were performed at the age of 28 days. The test results of SCC mixes revealed that, the flowability increases with increase in fly ash content and the compressive strength decreases with increase in water-binder ratio. It is concluded that a combination of fly ash, silica fume and GGBS in SCC can be used to make a sustainable, eco-friendly construction material for a better tomorrow.